2019
DOI: 10.1101/718643
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

WITHDRAWN: Complementary functions of the mechanosensitive factorsegr1,klf2bandklf2ainstruct the endocardial program

Abstract: Mechanical forces are key modulators of valvulogenic developmental programs. However, the mechanosensitive gene network underlying this process remains unclear. It is well established that contractile and flow forces activate endocardial expression of the transcription factor klf2a during valve morphogenesis. We report two novel transcription factors with a function in heart valve formation in zebrafish: egr1 and klf2b. Genomewide analysis of gene expression reveals that the endocardial transcriptional program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…In this context, it would be interesting to assess whether double and triple mutants of the channels described in our study would display calcium pulse phenotypes in addition to the enrichment defect. We also found that the pkd genes cooperate to repress the AV endocardial expression of the transcription factor genes klf2a and klf2b, which are essential for valve formation 7,19,22 . This observation suggests that the expression level of these transcription factors must be tightly regulated and that higher levels of their expression negatively affect AV valve formation.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations
“…In this context, it would be interesting to assess whether double and triple mutants of the channels described in our study would display calcium pulse phenotypes in addition to the enrichment defect. We also found that the pkd genes cooperate to repress the AV endocardial expression of the transcription factor genes klf2a and klf2b, which are essential for valve formation 7,19,22 . This observation suggests that the expression level of these transcription factors must be tightly regulated and that higher levels of their expression negatively affect AV valve formation.…”
Section: Discussionmentioning
confidence: 62%
“…Although Klf2a targets have been studied in the myocardium and endocardium during zebrafish valve development 7,[19][20][21][22] , the intermediates of Pkd and Klf2a remained unknown. Here, we identified the camk2g genes as upstream mediators of klf2a expression and downstream effectors of Pkd proteins during AV valve elongation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations